Identifikasi Sumber Belajar Lokal untuk Mendukung Inovasi Pembelajaran Biologi - Nurhidayati, Siti (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
This research aims to identify local learning resources as an effort to support innovation in high school biology teaching in Mataram City and West Lombok Regency. This study involves exploration using observation and interviews with teachers and students to collect data on the potential of local learning resources and their application in biology education. The results indicate that there are various potential local learning resources, such as school gardens, city parks, urban forests, coastal areas, and local agro-tourism sites. The identification and utilization of these local learning resources have proven to enhance students' interest and motivation, as well as provide a more contextual and relevant learning experience. Data analysis shows that while there is significant potential in utilizing local learning resources, there are still challenges in its implementation.